Review of Ontology, Epistemology, and Axiology in Research Articles on Implementing Digital Literacy in Students' Online Learning Activities - Zam, Efvy Zamidra; Herlina, Vivi; Sandra, Elvina; R, Ferdinal (Jurnal Basicedu, 2024)
Digital literacy is a competency that should be mastered by various education sectors, from primary education to higher education. This study aims to examine research entitled Analysis of the Application of Digital Literacy in Student Online Learning Activities. This study was reviewed based on ontology, epistemology, and axiology. The method of this study was content analysis, the object of which is the application of digital literacy in student online learning activities. This study found that the research still needs to fulfill the ontology principle. Furthermore, the epistemological principle is sufficiently fulfilled, and only a few deficiencies can be adjusted. Finally, the axiological principle is fulfilled because it contains several values that can be derived from this research. This study's implications are that the government should provide infrastructure and tools to increase digital literacy in Indonesia.